Love is my favorite flavor : a Midwestern dining critic tells all - Moranville, Winifred (Iowa City : University of Iowa Press, 2024)
"Immerse yourself in a fascinating culinary journey through American dining from the mid-1970s through today. In a remarkable career that has spanned nearly 50 years, Wini Moranville has witnessed the American restaurant landscape transform from the inside out. At just shy of 14, she began a 10-year stretch working in a kaleidoscope of quintessential Midwestern eateries of the time. From the familiarity and warmth of a family-owned cafeteria, to the groovy vibe of a hippie-run vegetarian restaurant, from the graciousness of a department store tearoom, to the camaraderie of a downtown coffeeshop, and later, the dispiriting milieu of an exclusive private dining club, Moranville's hands-on experiences weave a vivid tapestry of the American restaurant landscape in the 1970s and 80s. In the mid-90s, the tables turned as Moranville became a prolific food and wine writer for national publications, as well as the dining critic for the Des Moines Register and later, dsm Magazine. During the past 25 years, she has written over 750 professional restaurant reviews. Here, she tells of the great evolution of the American dining scene that happened on her watch, as food become more ambitious, energetic, locally sourced, and globally purveyed. She also recounts, with humor and heart, the pleasures and pitfalls of being a well-known and highly trusted food critic, when, for instance, a readers will corner you at the supermarket if they disagree with what you've written. Amidst the vast changes that have occurred over the years, the book underscores the timelessness of what it is we seek when we entrust restaurateurs with our hard-earned money and our hard-won leisure time. Dining out may have changed dramatically since the 70s, but the joys of being in the hands of people who care deeply about our time at their tables have not"--
13. Salad Days in New York City -- 14. My France Problem -- 15. Confessions of a Reluctant Wine Writer -- 16. It All Sprang from the Good Earth -- 17. Reader, I Did It All for You -- 18. Cheap Wine in the Open Air -- Epilogue: The Greatest Meals in the World -- Acknowledgments
Description based on online resource; title from digital title page (viewed on June 04, 2024).
JSTOR
Keywords: Restaurants -- United States -- History; Dinners and dining -- United States -- History; Restaurants -- États-Unis -- Histoire; BIOGRAPHY & AUTOBIOGRAPHY / General